2009
DOI: 10.1111/j.1600-0528.2008.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing caries experience among adults with physical and intellectual disabilities

Abstract: Residential setting was not associated with caries experience. Modifiable risk factors were diet, frequency of dental visits, no OHA and carer-contact hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 6 publications
5
43
2
3
Order By: Relevance
“…Many reports have shown that individuals with ID have worse oral hygiene and higher rates of dental disease as compared with the general population (2)(3)(4). Until recently, studies of dental caries in individuals with ID primarily focused on children (5,6), although concerns regarding affected adults have recently been discussed (7). The oral health status of individuals with ID is related to their cognitive patterns, developmental anomalies (8), and a variety of other factors, including age, type of caregiver, and physical disability (3).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that individuals with ID have worse oral hygiene and higher rates of dental disease as compared with the general population (2)(3)(4). Until recently, studies of dental caries in individuals with ID primarily focused on children (5,6), although concerns regarding affected adults have recently been discussed (7). The oral health status of individuals with ID is related to their cognitive patterns, developmental anomalies (8), and a variety of other factors, including age, type of caregiver, and physical disability (3).…”
Section: Introductionmentioning
confidence: 99%
“…16 In the present study, sugar intake was not shown to be significantly associated with caries experience, which disagrees with most findings in the literature. 15 However, a recent systematic review suggested that the relationship between sugar consumption and caries is presently less substantial than it was in the past. 17 One study 16 showed that female gender is a predisposing factor for dental caries, especially in the permanent dentition of disabled individuals.…”
mentioning
confidence: 99%
“…14 Nonetheless, the assistance and support of others is fundamental to the maintenance of oral health, 1 which is supported by the fact that a greater caries experience is observed in individuals with no oral hygiene assistance. 15 Along with physical limitations, individuals with CP may also exhibit some degree of cognitive impairment, which further hinders the adoption of adequate oral hygiene practices. 13 Such patients are often unable to follow instructions or understand the importance of maintaining satisfactory oral hygiene.…”
mentioning
confidence: 99%
“…In addition, a Swiss study found a higher incidence of dental caries (tooth decay) among adults with ID who lived with family as compared to their counterparts in institutional settings (Gabre & Gahnberg, 1994). In a more recent study, adults who lived with their families were more likely to receive needed assistance with daily dental hygiene than their institutionalized counterparts, but were less likely to receive regular preventive care from a dentist (Pradhan, Slade, & Spencer, 2009). However, family relationships are also an important source of support for people with ID (Orsmond et al, 2006).…”
Section: Introductionmentioning
confidence: 96%